Deletion of Robo4 prevents high‐fat diet‐induced adipose artery and systemic metabolic dysfunction. (5th April 2019) - Phuong, Tam T. T.; Walker, Ashley E.; Henson, Grant D.; Machin, Daniel R.; Li, Dean Y.; Donato, Anthony J.; Lesniewski, Lisa A.
Abstract: Objective: Accumulating evidence suggests the vascular endothelium plays a fundamental role in the pathophysiology of obesity by regulating the functional status of white adipose and systemic metabolism. Robo4 is expressed specifically in endothelial cells and increases vascular stability and inhibits angiogenesis. We sought to determine the role of Robo4 in modulating cardiometabolic function in response to high‐fat feeding. Methods: We examined exercise capacity, glucose tolerance, and white adipose tissue artery gene expression, endothelium‐dependent dilation (EDD), and angiogenesis in wild type and Robo4 knockout (KO) mice fed normal chow (NC) or a high‐fat diet (HFD). Results: We found Robo4 deletion enhances exercise capacity in NC‐fed mice and HFD markedly increased the expression of the Robo4 ligand, Slit2, in white adipose tissue. Deletion of Robo4 increased angiogenesis in white adipose tissue and protected against HFD‐induced impairments in white adipose artery vasodilation and glucose intolerance. Conclusions: We demonstrate a novel functional role for Robo4 in endothelial cell function and metabolic homeostasis in white adipose tissue, with Robo4 deletion protecting against endothelial and metabolic dysfunction associated with a HFD. Our findings suggest that Robo4‐dependent signaling pathways may be a novel target in anti‐obesity therapy.